Right To Education And Teacher Gap In Nigeria: Estimating The Problem And Lessons From International Best Practices - Nwokeocha, Steve (Advances in Social Sciences Research Journal, 2018)
This paper was first presented as the 2018 Distinguished Guest Paper at Nigeria’s Annual World Teachers’ Day Symposium. The theme of the 2018 World Teachers’ Day, which is “Right to education means the right to a qualified teacher” therefore, provides the context. The paper examines the main thrusts of the 1966 International Labour Organisation (ILO)/United Nations Educational, Scientific and Cultural Organisation (UNESCO) Recommendation concerning the Status of Teachers and 1997 UNESCO recommendation concerning the status of higher education teaching personnel which laid a strong foundation for the professionalization of teaching and gave birth to the World Teachers’ Day. It argues that the theme of the World Teachers’ Day calls for a balance between the promises of the right to education and implementation of the 1996 ILO/UNESCO and 1997 UNESCO Recommendations. Against this background, the paper x-rays the concept and dimensions of the right to education as intended by the international conventions and international education goals. It also discusses the approaches to determining out-of-school children and interrogates the figures of out-of-school children and the teacher gap in Nigeria. It finally discusses some international best practices regarding the right to education and the strategies of the African authorities to tackle the teacher gap in the continent and provides some recommendations for Nigeria.